2006
DOI: 10.1002/glia.20378
|View full text |Cite
|
Sign up to set email alerts
|

Different expression of synemin isoforms in glia and neurons during nervous system development

Abstract: The synemin gene encodes proteins belonging to the intermediate filament family. These proteins confer resistance to mechanical stress and modulate cell shape. Three synemin isoforms, of 180 (H), 150 (M) and 41 (L) kDa, are produced by alternative splicing of the pre-mRNA and are regulated differently during development. The three isoforms differ in their C-terminal tail domains, while their IF rod domains are identical. Synemins H/M occurred together with nestin and vimentin in glial progenitors during the ea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
34
2

Year Published

2007
2007
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(39 citation statements)
references
References 31 publications
3
34
2
Order By: Relevance
“…1A-B) and 14 days (data not shown) after lesioning. No synemin immunoreactivity was seen on the uninjured site (data not shown), which is in agreement with recent findings showing that ␣-and ␤-synemin are not present in the dentate gyrus of normal, adult mice (Izmiryan et al, 2006). Synemin and GFAP immunoreactivity colocalized in reactive astrocytes both in the denervated dentate gyrus (Fig.…”
Section: Vimsupporting
confidence: 93%
“…1A-B) and 14 days (data not shown) after lesioning. No synemin immunoreactivity was seen on the uninjured site (data not shown), which is in agreement with recent findings showing that ␣-and ␤-synemin are not present in the dentate gyrus of normal, adult mice (Izmiryan et al, 2006). Synemin and GFAP immunoreactivity colocalized in reactive astrocytes both in the denervated dentate gyrus (Fig.…”
Section: Vimsupporting
confidence: 93%
“…Interestingly, this membrane defect could be indirectly related to the absence of synemin and be the result of perturbation of its interaction with proteins that might be directly involved in the integrity of membrane structure, such as dystrophin, utrophin, adystrobrevin, plectin 1, zyxin, vinculin and talin (Bellin et al, 1999;Bhosle et al, 2006;Hijikata et al, 2008;Mizuno et al, 2001;Sun et al, 2008a;Sun et al, 2008b;Sun et al, 2010a). It has been reported that b-synemin mediates the association of desmin IFs with Z-lines in neonate cardiomyocytes, whereas a-synemin stabilises junctional complexes between cardiomyocytes (Lund et al, 2012), and synemin L binds to neurofilaments associated with the membrane compartment in adult mouse spinal cord (Izmiryan et al, 2006). We cannot know yet which synemin isoform is more important for membrane integrity because our Synm 2/2 model is null for all forms of synemin.…”
Section: Synemin Is Necessary For Sarcolemmal Membrane Integrity and mentioning
confidence: 99%
“…An exception is the protein synemin. First identified as a high-molecular-mass protein associated with desmin and vimentin filaments in muscle (Granger and Lazarides, 1980), synemin expression was later detected in different tissues and cell types, including the nervous system, endothelial cells, retinal cells and hepatic stellate cells (Hirako et al, 2003;Izmiryan et al, 2006;Izmiryan et al, 2009;Izmiryan et al, 2010;Schmitt-Graeff et al, 2006;Tawk et al, 2003;Uyama et al, 2006). Three synemin isoforms differing in their C-terminal tails -a-synemin (also known as synemin H, 180 kDa), b-synemin (also known as synemin M, 150 kDa) and synemin L (41 kDa) -are produced by alternative splicing and are differentially regulated during embryonic development (Titeux et al, 2001;Xue et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…One possibility is that there is an additional neurofilament subunit, as yet unidentified, that interacts with the neurofilament motors and that this subunit is common to all neurofilaments. In fact, recent studies indicate that neurons may also express an alternately spliced isoform of the intermediate filament protein synemin, termed synemin L [Izmiryan et al, 2006], so it is quite possible that we do not yet know the full extent of the complexity of neurofilament composition. However, it seems more likely that the neurofilament motors are capable of interacting with multiple different neurofilament protein subunits.…”
Section: Discussionmentioning
confidence: 99%